Performance of healthcare providers regarding iranian women experiencing physical domestic violence in Isfahan - Nasim Yousefnia; Nafisehsadat Nekuei; Ziba Farajzadegan; Ghasem Yadegarfar (Wolters Kluwer Medknow Publications, 2018)
Background: Domestic violence (DV) can threaten women's health. Healthcare providers (HCPs) may be the first to come into contact with a victim of DV. Their appropriate performance regarding a DV victim can decrease its complications. The aim of the present study was to investigate HCPs' performance regarding women experiencing DV in emergency and maternity wards of hospitals in Isfahan, Iran. Materials and Methods: The present descriptive, cross-sectional study was conducted among 300 HCPs working in emergency and maternity wards in hospitals in Isfahan. The participants were selected using quota random sampling from February to May 2016. A researcher-made questionnaire containing the five items of HCPs performance regarding DV (assessment, intervention, documentation, reference, and follow-up) was used to collect data. The reliability and validity of the questionnaire were confirmed, and the collected data were analyzed using SPSS software. Cronbach's alpha was used to assess the reliability of the questionnaires. To present a general description of the data (variables, mean, and standard deviation), the table of frequencies was designed. Results: The performance of the participants regarding DV in the assessment (mean = 64.22), intervention (mean = 68.55), and reference stages (mean = 68.32) were average. However, in the documentation (mean = 72.55) and follow-up stages (mean = 23.10), their performance was good and weak respectively (criterion from 100). Conclusions: Based on the results, because of defects in providing services for women experiencing DV, a practical indigenous guideline should be provided to treat and support these women.